Anti-Müllerian hormone and inhibin B dynamics in polycystic ovary syndrome: correlation with controlled ovarian hyperstimulation outcomes and pregnancy success - Li, Yueying; Han, Lu; He, Ying; Li, Xiaoyan; Zhang, Yan; Zhang, Huiying; Wang, Yingmei; Zhang, Huijuan; Tian, Wenyan (Frontiers in Endocrinology, 2025)
PurposeTo investigate the dynamic changes of serum Anti-Müllerian Hormone (AMH) and Inhibin B (INHB) during controlled ovarian hyperstimulation (COH) in patients with polycystic ovarian syndrome (PCOS) and analyze their correlation with COH outcomes and pregnancy success.MethodsA total of 40 individuals diagnosed with PCOS and 40 control subjects were recruited for the study. Serum concentrations of AMH and INHB were quantified at several key time points: at the initiation of gonadotropin treatment (dGn), on the fifth day of stimulation (dGn5), on the day of hCG administration (dhCG), on the day of oocyte pick-up (dOPU), and within the follicular fluid (FF) collected on the day of oocyte retrieval, employing the ELISA method for analysis. The changes in their concentrations were explored, and their correlations with COH outcomes and pregnancy success were analyzed.ResultsAMH peaks on the basal day and subsequently declines during the COH procedure. The serum AMH levels are consistently correlated with basel testosterone(T), antral follicle count(AFC), estradiol (E2) on the trigger day, retrieved oocytes, two pronuclei (2PN) fertilization, available embryos, top-quality embryos (TQE) and TQE rate (p<0.05). INHB elevates during the COH process, peaks at dHCG, and thereafter declines. Serum levels are closely associated with AFC, E2 on the trigger day, retrieved oocytes, 2PN fertilizations, available embryos and TQE rate(p<0.05). During COH, AMH and INHB in both FF and serum are interrelated. AMH levels on dOPU (β=-5.2250, P=0.0014) and INHB levels on dOPU (β=-0.1106, P<0.05) were significant negative predictors of the TQE rate. Serum INHB at dGn5 demonstrated predictive value for pregnancy outcomes (AUC = 0.71, 95% confidence interval: 0.59–0.83).ConclusionDuring COH, serum AMH and INHB exhibit cyclical variations. Serum AMH and INHB especially on dOPU are closely associated with the outcomes of COH. They possess the capacity to predict the results of COH. Moreover, serum INHB (dGn5) may serve as a potential biomarker for individualized prediction of pregnancy success in PCOS patients.